"Digital Health Diplomacy" in Global Digital Health? A call for critique and discourse. (20th December 2021) - Godinho, Myron Anthony; Martins, Henrique; Al-Shorbaji, Najeeb; Quintana, Yuri; Liaw, Siaw-Teng
Abstract: Actualizing the vision of Global Digital Health is a central issue on the Global Health Diplomacy agenda. The COVID-reinforced need for accelerated digital health progress will require political structures and processes to build a foundation for Global Digital Health. Simultaneously, Global Health Diplomacy uses digital technologies in its enactment. Both phenomena have driven interest in the term "Digital Health Diplomacy." A review of the literature revealed 2 emerging but distinct definitions that have been published very recently, each with its associated discourse and practice. This multiplicity of ideas demonstrates the myriad ways in which global digital and political systems are becoming increasingly entangled. Untangling these, this paper proposes and discusses 3 dimensions of Digital Health Diplomacy: "Diplomacy for digital health, " "Digital health for diplomacy, " and "Digital health in diplomacy." It calls upon digital health professionals, diplomats, political and social scientists, epidemiologists, and clinicians to discuss, critique, and advance this emerging domain.